The intercultural mexiquense university and rural and indigenous communities. Strategies of rapprochement and linkage experiences - Erdosova, Zuzana (2021)
The educational model of the intercultural university aims at the construction of knowledge in conditions of equity and dialogue with indigenous peoples, however, due to the neoindigenist ideological load of the educational model, the theoretical approach and actual practices often diverge. For this reason, the article analyzes the ways in which a specific university, the Intercultural University of the State of Mexico, relates to the indigenous communities of the region. This analysis is carried out through the testimonies of a series of indigenous and non-indigenous protagonists, involved in the processes of Community Liaison, one of the axes of the educational model. It is concluded that the university-community relationship is characterized, on the one hand, by the openness of the University to the initiatives arising from the communities, including the students who come from them, but, on the other hand, by a modernizing attitude that gives priority to the notions of economic development understood in neoliberal terms before the cultural autonomy of the development of the native peoples. In this sense, demystifying the hegemonic educational discourses becomes of primary importance to ensure the transparency of the educational system and its functionality in the context of ethnic diversity.